2004
DOI: 10.4315/0362-028x-67.3.475
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of an Antimicrobial Packaging Film Coating Containing Nisin for Inhibition of Listeria monocytogenes

Abstract: The purpose of this study was to develop and characterize a packaging film coating containing nisin. A spot-on-lawn assay was used to determine the effect of acid type (ascorbic, acetic, hydrochloric, lactic) and nisin level (equal increments from 10,000 IU to 9 IU) to be used in the formulation of the film coating. Zones of inhibition were measured after incubation on tryptic soy agar (37 degrees C, 48 h). Low-density polyethylene films coated with differing levels of nisin were characterized by field emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Once again the relatively small mass of the bacterial cells, compared to the total mass of the polymeric matrix, can explain why the WVP is not affected by the presence of the cells. Similarly, it has been reported in previous studies that addition of antimicrobial agents, such as nisin, at low concentrations did not cause significant changes in the WVP of SC films (Kristo et al, 2008) or LPDE films coated with a nisin-incorporated cellulose-based coating (Grower, Cooksey & Getty, 2004).…”
Section: Water Vapor Permeabilitymentioning
confidence: 72%
“…Once again the relatively small mass of the bacterial cells, compared to the total mass of the polymeric matrix, can explain why the WVP is not affected by the presence of the cells. Similarly, it has been reported in previous studies that addition of antimicrobial agents, such as nisin, at low concentrations did not cause significant changes in the WVP of SC films (Kristo et al, 2008) or LPDE films coated with a nisin-incorporated cellulose-based coating (Grower, Cooksey & Getty, 2004).…”
Section: Water Vapor Permeabilitymentioning
confidence: 72%
“…They observed that packaging films coated with a cellulose-based solution containing 10,000 and 7,500 IU/ml nisin, respectively, significantly decreased (P<0.05) L. monocytogenes on the surface of hot dogs by more than 2 log CFU per package throughout the 60-day study. Grower et al (2004) analyzed antimicrobial packaging film coating containing nisin for the inhibition of L. monocytogenes using low-density polyethylene films coated with differing levels of nisin. Luchansky and Call (2004) evaluated nisin-coated cellulose casings for the control of L. monocytogenes inoculated onto the surface of commercially prepared frankfurters, finding that the levels of the pathogen decreased by 0.88 log CFU per package after 15 days of storage but then increased appreciably over a 60-day period of refrigerated storage.…”
Section: Bacteriocins In Antimicrobial Filmsmentioning
confidence: 99%
“…Therefore, GRS (generally recognized as safe) substances such as sorbic acid (Cagri, Ustunol, & Ryser, 2001;Limjaroen, Ryser, Lockhart, & Harte, 2003), benzoic acid, propionic acid (Quattara, Simard, Piette, Bégin, & Olley, 2000b;Soares, Rutishauser, Melo, Cruz, & Andrade, 2002) and its salts (Buonocore, Del Nobile, Panizza, Corbo, & Nicolais, 2003;Choi et al, 2005;Ozdemir & Floros, 2001) nisin (Dawson, Hirt, Rieck, Acton, & Sotthibandhu, 2003;Grower, Cooksey, & Getty, 2004;Lee, Soon, Lee, Park, & Lee, 2004;Melo, 2003), and others have been incorporated into polymers for the production of antimicrobial packaging. Weng and Hotchkiss (1993) incorporated 1% of benzoic anhydrous into low-density polyethylene Wlms, inhibiting completely the growth of Rhyzopus stolonifer, Penicillium spp.…”
Section: Introductionmentioning
confidence: 98%